Persepsi siswa terhadap pelaksanaan pembelajaran daring/e-learning pada mata pelajaran Biologi di kelas XI IPA SMA Negeri 2 Pekanbaru tahun ajaran 2020/2021 - Tengku Idris; Nur Sedala Putri (Universitas Islam Riau (UIR) Press, 2022)
This study aims to determine students' perceptions of the implementation of online learning / e-learning in Biology subjects in class XI IPA SMA Negeri 2 Pekanbaru for the 2020/2021 academic year. This research is a descriptive quantitative research with the type of research used a survey. Data collection was carried out by distributing questionnaires, interviews, observation sheets and documentation. This study used a saturated sample that included all members of class XI Sciensi 1, XI Science 2, XI Science 3, and XI Science 4 Senior High School 2 Pekanbaru as many as 143 students. The questionnaire distributed consists of 40 statements consisting of four aspects of assessment with eleven indicators. Based on the results of the study, the aspect of assessing student attitudes was categorized as sufficient with a percentage of 61.97%. The aspect of assessing the principles of online learning / e-learning has a sufficient category with a percentage of 65.73%. The aspect of competency assessment related to online / e-learning has a sufficient category with a percentage of 72.26% and the infrastructure assessment aspect is in a good category with a percentage of 76.33%. It can be concluded that students' perceptions of the implementation of online learning / e-learning in Biology subjects in class XI IPA SMA Negeri 2 Pekanbaru in the academic year 2020/2021 as a whole are in the sufficient category with a percentage of 69.47%.